Tityus fasciolatus e Tityus Serrulatus: caracterização eletrocardiográfica e laboratorial do envenenamento em ratos - Mariana Cunha Longuinhos Pinto (2009)
Scorpion sting is a public health problem and causes high lethality in young individuals. This study was performed to characterize the envenomation by Tityus fasciolatus, endemic specie in Minas Gerais State and Brazil Central (study I) and by T. serrulatus, the most important specie in Brazil (study II). Twelve male Wistar rats, 130g, were distributed into two groups (n=6): 400µl placebo (control group), and 300µg of T. fasciolatus venom/animal to perform study I. Other 15 animals were distributed into three groups (n=5): 400µl placebo (control group); 100µg of T. serrulatus venom/animal; and 450µg/animal, for the study II. Electrocardiographic exams were performed before and every 5 min during 30 min after envenomation, blood profile (hematology, electrophoresis and serum biochemistry), macroscopic and microscopic alterations in brain, lungs and heart. All envenomated animals showed pain immediate, ECG changes suggesting electrolytic imbalance, myocarditis and action in conduct tissue; laboratorial results showed neutrophilia and myocardial damages; and pulmonary hemorrhages. Low insulin levels and acute renal failure occurred in rats inoculated with T. serrulatus venom. In conlusion, T. fasciolatus and T. serrulatus venoms caused cardiorespiratory changes in young rats